A study on microscopic damage characteristics of freeze-thaw sandstone cyclic loading and unloading based on DEM - Sun, Lichen; Lou, Peijie; Pan, Cheng; Ji, Penghui (Frontiers in Materials, 2024)
With the goal of examining the micromechanics damage characteristics of freeze-thaw red sandstone under the influence of cyclic loads, a model of freeze-thaw cyclic rock particles is developed based on Discrete Element Method numerical simulation in order to investigate and study the micromechanics response mechanism of rocks under the coupling effect of freeze-thaw and cyclic loads. The findings demonstrate that lower rock elastic modulus and higher irreversible strain are driven by longer loading/unloading durations and more frequent freeze-thaw cycles. Its bearing capacity and resistance to deformation are diminished by the damage brought on by freeze-thaw; Rock anisotropy and the spatial organisation of microcracks are significantly altered by different loading techniques; In freeze-thaw rocks, the frequency and intensity of acoustic emission breaking follow the law of normal distribution. Under cyclic stress, samples exposed to several freeze-thaw cycles exhibit an escalation in large-scale fractures, accompanied by a concentrated spatial distribution of acoustic emission events. Three phases may be distinguished in the energy evolution of red sandstone: the initial, accumulation, and release phases. The energy storage capacity is compromised by freeze-thaw degradation, resulting in an elevated conversion rate of dissipative energy and rendering the energy conversion mechanism more unstable. The previously described study results possess considerable relevance for rock engineering construction and catastrophe mitigation in cold climates.